2020
DOI: 10.1152/jn.00623.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sequential activation of multiple persistent inward currents induces staircase currents in serotonergic neurons of medulla in ePet-EYFP mice

Abstract: Persistent inward currents (PICs) are widely reported in rodent spinal neurons. A distinctive pattern observed recently is staircase-like PICs induced by voltage ramp in serotonergic neurons of mouse medulla. The mechanism underlying this pattern of PICs is unclear. Combining electrophysiological, pharmacological, and computational approaches, we investigated the staircase PICs in serotonergic neurons of medulla in ePet-EYFP transgenic mice (postnatal days 1–7). Staircase PICs induced by 10-s voltage biramps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that PICs play an important role in regulating neuronal excitability and firing patterns in spinal motoneurons and interneurons (Theiss et al, 2007 ; Heckman et al, 2008 ). Recently, we found the presence of PICs in 5-HT neurons in the mesencephalic locomotor region and medulla of neonatal ePet-EYFP mice (Ge et al, 2019 ; Cheng et al, 2020 ). In this study, we further explored whether PICs presented in 5-HT neurons of DRN in juvenile mice as well as the effects of exercise training on PICs.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous studies have shown that PICs play an important role in regulating neuronal excitability and firing patterns in spinal motoneurons and interneurons (Theiss et al, 2007 ; Heckman et al, 2008 ). Recently, we found the presence of PICs in 5-HT neurons in the mesencephalic locomotor region and medulla of neonatal ePet-EYFP mice (Ge et al, 2019 ; Cheng et al, 2020 ). In this study, we further explored whether PICs presented in 5-HT neurons of DRN in juvenile mice as well as the effects of exercise training on PICs.…”
Section: Resultsmentioning
confidence: 93%
“…Both modeling and experiment studies suggested that these changes in Vth and AP amplitude could be produced by upregulating transient sodium channels (Dai et al, 2002 ; Power et al, 2012 ). Results from recent studies showed that riluzole, a Na-PIC blocker, significantly depolarized the Vth of 5-HT neurons (Svensson et al, 2017 ; Cheng et al, 2020 ), suggesting that persistent sodium channels modulate Vth (Dai et al, 2002 ; Power et al, 2012 ). In fact, transient sodium channels and persistent sodium channels are considered to originate from the same ion channels with different kinetics for activation and inactivation (Crill, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations